Assessment Of The Efficacy Of Pelvis External Immobilization Device And Short Wave Diathermy In The Management Of Pelvic Fractures In Kids - Velavan, A.; Pushkinraj, H. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Eighteen kids with pelvic fracture were divided into three groups containing six animals each. Fractures of the tuber coxae, wing of the ilium, tuber ischii and ischeal shaft were selected for the study and allotted randomly to each group. First group was treated by medications. Second group was treated by medication and Short Wave Diathermy. Third group was treated by medication and Pelvis External Device Immobilization. All the animals were tested based on the parameters like recumbence, weight bearing, pain perception and radiographic bone healing for six weeks period. Results revealed that Diathermy group developed complete bridging callus in three animals and Pelvis External Immobilization group developed complete bridging callus in five animals. This study revealed that even though diathermy helps in pelvic fracture healing, Pelvis External Immobilization favors better fracture healing.
Keywords: Pelvic fracture; kid; Pelvic External Immobilization Device; Short Wave Diathermy